FEATURES OF THE COURSE OF DISEASES ASSOCIATED WITH HELICOBACTER PYLORI INFECTION IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article is devoted to the features of the course of diseases associated with Helicobacter Pylori (HP) infection in children. The data of epidemiological studies are presented, showing the prevalence of the prevalence of chelicobacteriosis in children. In accordance with international standards, the main treatment regimens used for eradication therapy are given.